Influence of the design parameters of the mincer on the rheological properties of minced meat - Stukalska (Ivanova), Nataliia (My University, 2021)
The process of grinding and obtaining high-quality minced meat with the specified structural and mechanical properties is influenced by the relationship of the design parameters of the meat grinder. Interest was expressed in expanding the range of use of design parameters and studying their impact on the structural and mechanical properties of minced chicken meat and technological parameters of the grinding process. Chicken meat was used as raw meat, which was divided into types: fillet, leg meat and a mixture of fillet + leg meat in a ratio of 1: 1.
Keywords: mincing process; meat grinder; rheological properties; minced meat; процес подрібнення; м’ясорубка; м’ясний фарш; реологічні властивості; кафедра технології ресторанної і аюрведичної продукції